Self-Medication and Contributing Factors: A Questionnaire Survey Among Iranian Households - Ezzatabadi, Mohammad Ranjbar; Rafiei, Sima; Shafiei, Milad; Tafti, Arefeh Dehghani; Saghafi, Fatemeh; Bahrami, Mohammad Amin; Abdarzadeh, Nadia (BALI MEDICAL JOURNAL; Vol 5 No 3 (2016), 2016)
Background: Self-medication is a serious danger in every health sector which potentially brings harmful side effects for the society. The aim of this research was to investigate self-medication and its contributing factors among residents of Yazd province in Iran in 2014. Methods: A descriptive, cross sectional study was conducted in 2014 using a self-constructed questionnaire. A total of 580 families living in Yazd in the time period of study were contributed to fill out the questions organized in two sections of demographic and self-medication factors. Data were analyzed by SPSS software version 16 through appropriate descriptive and analytical statistical tests. Results: Self-medication was reported in 53.4% of the cases. The most frequent self-prescribed medications were related to pain killer drugs (26.6%). There was a significant statistical relation between self-medication and households’ age, occupation and income, level of parents’ education, number of children and place of residence. Among different reasons for self-medication the most important one was reported to be accessibility (3.44+1.3). Conclusion: Due to the considerable prevalence of self-medication and its harmful effects on every society, such an issue should be appropriately controlled through legal regulations particularly in the area of selling dangerous drugs. Furthermore, provision of proper information and warning the population about harmful side effects can be helpful in this regard.
Keywords: Self-medication, contributing factor, prevalence.